The trade effects of European antidumping policy - Arastou Khatibi (European Centre for International Political Economy (ECIPE), 2009)
This paper empirically studies the effects of European antidumping actions on import diversion from importers named in an antidumping investigation, and potentially subject to protectionist measures, to countries not named in the investigation and European domestic suppliers. For this purpose, a unique data set is used at the 8-digit product level. The amount of import diversion from named countries to the EU domestic market can be read as how well antidumping policy benefits EU producers. This paper shows that although antidumping protection predominantly benefits the EU domestic market rather than non-named countries, it is not strong enough to offset the decrease in imports from named countries. In addition, using a measure based on Balassa's index of revealed comparative advantage, trade effects where EU suppliers have a comparative advantage versus a disadvantage are also examined. When EU members reveal a comparative disadvantage, antidumping becomes more restrictive for named countries, and there is no evidence of trade diversion to non-named countries. Consequently, the overall trade depressing effect is stronger. On the other hand, the analysis provides some evidence that intra-EU trade activity becomes more intensive, suggesting that antidumping protection is good for disadvantaged products.
Keywords: F13; L5; L13; 330; Antidumping measures; Trade Diversion; Revealed Comparative Advantage